Effects of a protocol of virtual reality exercice in the balance and functional independence of individuals with Parkinson Disease – clinical study - Freitas, Nei Adão Ribeiro de (2018)
ABSTRACT: The present study aimed to analyze the effects of Virtual Reality (VR) on the balance and functional independence of individuals with moderate stage Parkinson 's disease (PD). The sample consisted of 4 individuals, with clinical diagnosis of PD. These were submitted to balance evaluation through the Berg Balance Scale (BBS) and functional independence, measured by the Functional Independence Measure (MIF). The result obtained in BSE on reevaluation after VR was statistically shown significant.